Population structure and phylogenetic analysis of Vibrio cholerae non-O1/O139 by whole genome sequencing - Taylor Wells; Elizabeth González-Durán; Anthony M. Smith; Swapan K. Banerjee; Sandeep Tamber; Natalie Knox; Celine Nadon (PLoS ONE, 2026)
Toxigenic Vibrio cholerae serogroups O1 and O139 are well known for causing excessive diarrhea leading to devastating cholera epidemics and pandemics. Over 200 other serogroups, usually lacking the cholera toxin, are denoted non-O1/O139 V. cholerae (NOVC), and cause vibriosis leading to sporadic gastroenteritis and other extraintestinal infections. NOVC infections are not a notifiable disease in Canada and thus underreported. From 2010 to 2023, 160 cases and a small 2018 outbreak were reported in Canada caused by NOVC, provoking considerable public health concern. In this study, 242 Canadian V. cholerae isolates were sequenced, characterized and compared with over 1500 other V. cholerae isolates from around the world to determine their genetic relationships. All Canadian NOVC and two O139 isolates lacked the cholera toxin-producing genes typically harbored by pathogenic O1 and O139. All 14 Canadian O1 isolates were identified from travel-related cases as members of the toxigenic 7 th pandemic lineage, whereas one O139 isolate was acquired domestically. Phylogenetic analysis based on core genome single nucleotide polymorphisms classified the Canadian isolates into five clades. Eight new lineages of NOVC, denoted CAD1–8, were identified from the Canadian isolates. A new lineage was defined as clusters formed by three or more isolates in the phylogeny. These lineages were comprised of isolates from clinical origin alone, environmental origin, or a mixture of both. Some lineages spanned multiple years and regions. CAD-2 was comprised of clinical and environmental isolates associated with the 2018 outbreak. Several virulence genes were detected among NOVC, including hemolysins, toxins and secretion system encoding genes. A proportion of virulence genes differed between isolation source (clinical or environmental) and clinical manifestations (gastrointestinal or extraintestinal). Our study identified environmental sources of NOVC with the potential to cause human infection. Tracking the emergence of NOVC with pathogenic potential is essential for understanding the risk to Canadians.